FORECASTING FUTURE ENROLLMENTS TO UNIVERSITIES OF NORTH CYPRUS THROUGH TREND CENTRALITY BASED ON FUZZY TIME SERIES - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
In this study, student enrollments to universities of North Cyprus are examined from 2000 to 2009. Future values are forecasted using trend centrality of actual and forecasted enrollments that are obtained by using fuzzy time series.